Investigation of drug resistance of caries-related streptococci to antimicrobial peptide GH12 - Li, Xinwei; Wang, Yufei; Jiang, Xuelian; Zeng, Yuhao; Zhao, Xinran; Washio, Jumpei; Takahashi, Nobuhiro; Zhang, Linglin (Frontiers in Cellular and Infection Microbiology, 2022)
Dental caries is associated with caries-related streptococci and antimicrobial agents have been widely used for caries control, but troubled by antibiotic resistance. This study aimed to investigate the intrinsic and acquired resistance of caries-related streptococci to antimicrobial peptide GH12, which was proven promising for caries control, and preliminarily explore the phenotypic changes and whole genome of stable acquired resistant strains. In this study, susceptibility assays and resistance assays were performed, followed by stability assays of resistance, to evaluate the intrinsic resistance and the potential resistance of caries-related streptococci. Then, the phenotypic changes of the stable acquired resistant strain were explored. The whole genome of the resistant strain was sequenced and analyzed by second-generation and third-generation high-throughput sequencing technologies. Streptococcus gordonii and Streptococcus sanguinis were intrinsically resistant to GH12 compared to cariogenic Streptococcus mutans. Acquired GH12 resistance in one S. sanguinis and four S. mutans clinical strains was transient but stable in one S. mutans strain (COCC33-14). However, acquired resistance to daptomycin (DAP) and chlorhexidine in all strains was stable. Furthermore, the COCC33-14 showed cross-resistance to DAP and delayed growth rates and a lower population. However, no drug-resistant gene mutation was detected in this strain, but 6 new and 5 missing genes were found. Among them, annotation of one new gene (gene 1782|COCC33-14R) is related to the integral component of the membrane, and one missing gene rpsN is associated with the metabolism and growth of bacteria. The results indicate that stable resistant mutants of caries-related streptococci could hardly be selected by exposure to consecutive sublethal GH12, but the risk still existed. Resistance in COCC33-14R is mainly related to changes in the cell envelope.